Vanishing fleece: adventures in American wool - Parkes, Clara (Abrams Press, 2019)
Clara Parkes presents a fast-paced account of the year she spent transforming a 676-pound bale of wool into commercial yarn, and the people and vanishing industry she discovered along the way.